The risk of malnutrition in patients with spinal cord injury during inpatient rehabilitation–A longitudinal cohort study - Flury, Irene; Mueller, Gabi; Perret, Claudio (Frontiers in Nutrition, 2023)
Background & Aims: Patients with spinal cord injury (SCI) show an increased risk of malnutrition. Studies found that about 50% of patients with a recent SCI are affected by malnutrition when they enter a rehabilitation institution. However, there is a lack of data during the course and at discharge of initial rehabilitation as well as missing knowledge about the factors promoting such a risk. The aim of this study was to assess the risk of malnutrition in individuals with SCI three months post injury and at the end of inpatient rehabilitation and to identify factors associated with a high risk of malnutrition. Methods: Retrospective, monocentric, longitudinal cohort study, using the data set of the Swiss Spinal Cord Injury Cohort Study and additional data from the patients' medical records. Individuals with SCI were assessed for the risk of malnutrition using the Spinal Nutrition Screening Tool three months post injury and at discharge from initial inpatient rehabilitation. Odds ratios (OR) for potential risk parameters were calculated. Results: Of the 252 participants included, 62% were at risk for malnutrition three months post injury and still 40% at discharge. Moderate to high risk of malnutrition was found regardless of age and BMI. The highest odds for an increased risk at 3 months post injury was identified in ventilator-dependent persons (OR 10.2). At discharge from inpatient rehabilitation, pressure injury (OR 16.3) was the most prominent risk factor. Conclusions: In the population with SCI the risk of malnutrition is widespread during inpatient rehabilitation, but also at discharge. Ventilated persons and persons with pressure injuries are clear risk groups and need special attention. Based on these findings and the known negative impact of malnutrition on clinical outcomes, the awareness of malnutrition should be increased in the population with SCI. Therefore, a regular and standardized screening of the malnutrition risk is highly recommended.